PELATIHAN PRODUK TAHU INOVATIF UNTUK MEMBANGUN KEMANDIRIAN EKONOMI MELALUI KREATIVITAS DI DESA KALIANYAR - Sofiatus Sobriyah; Saini Saini; Qoidul Khoir; R.A. Harum Sukmo Ningratna(; Alfina Wildatul Fitriyah (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Kalianyar Village, known as the center of the tofu manufacturing industry with 22 active tofu factories, has great economic potential. However, the products produced are mostly still in the form of traditional tofu, which does not provide added value and new business opportunities for the community. The purpose of this Community Service Program (PKM) is designed to empower mothers in the village by providing training in processing tofu into various innovative products with high economic value. This training method involves direct demonstrations, joint practice, and interactive discussions, participants are introduced to various tofu processing techniques into products such as thau donuts, tofu sticks, Kentucky tofu and tofu meatballs. This training not only focuses on the technical aspects of processing, but also on marketing strategies to increase product competitiveness in local and regional markets. The results of this activity show an increase in participants' skills in processing tofu and the emergence of initiatives to start small businesses based on tofu processing. The positive impact of this program can be seen from the opening of new business opportunities that are expected to contribute significantly to improving the economy of families and communities in Kalianyar Village.